Embedded Systems Security: A Survey of EU Research Efforts. Issue 11 (23rd December 2014) - Manifavas, Charalampos; Fysarakis, Konstantinos; Papanikolaou, Alexandros; Papaefstathiou, Ioannis
Abstract Embedded systems security is a recurring theme in current research efforts, brought in the limelight by the wide adoption of ubiquitous devices. Significant funding has been allocated to various European projects on this subject area, in order to investigate and overcome the various security challenges. This paper provides an overview of recent EU research efforts pertaining to embedded systems security, where several prominent security issues and the respective proposed approaches are presented. Surveying relatively recent EU research projects, the authors identify 20 such projects that focus on embedded systems security aspects. The investigated technologies are categorised using a layered approach, to facilitate the presentation of the results; the categories comprise the node, network, and middleware and overlay layers, as well as architectures, frameworks and formal validation of the security of embedded systems. From this survey, certain patterns emerge regarding the issues investigated and the technologies researchers focus on, in order to address the said issues. Finally, the existing open issues are summarised, and directions for future research are given. Copyright © 2014 John Wiley & Sons, Ltd.